Development of a HPLC-MS/MS Method to Determine the 13 Elements of Semen Cuscutae and Application to a Pharmacokinetic Study in Rats. (6th November 2019) - Shen, Jiayuan; Jia, Qi; Huang, Xuhua; Yao, Guangzhe; Ma, Wenjuan; Zhang, Huamei; Ouyang, Huizi; He, Jun
Abstract : This study developed a method for simultaneous determination of 13 elements of Semen Cuscutae (quercitrin, quercetin, hyperoside, caffeic acid, chlorogenic acid, luteolin, apigenin, kaempferol, isoquercitrin, cryptochlorogenic acid, isorhamnetin-3- O -glucoside, astragalin, and rutin) in rat plasma using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) in the negative MRM mode. The analytes were analyzed with CORTECS®C18 column (4.6 × 150 mm, 2.7  μ m) with mobile phases consisting of 0.1% formic acid in water (A) and acetonitrile (B). The intra- and interday precision of the target compounds were expressed as relative standard deviation (RSD) in the range of 0.5%–10.4%, and the accuracy of the target compounds was expressed as relative error (RE) not exceeding ±14.5% for all analytes. In the meantime, the extraction recovery of the target compounds in plasma samples ranged from 87.4% to 106.2% and matrix effect from 81.0% to 115.5%. The established method was successfully accomplished for the pharmacokinetic study of the analytes in rat plasma samples following oral administration of Semen Cuscutae extract, and the pharmacokinetic parameters of seven compounds were obtained.